2020
DOI: 10.3389/fneur.2020.00599
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Nutritional Index for Predicting 3-Month Outcomes in Ischemic Stroke Patients Undergoing Thrombolysis

Abstract: Objective: Malnutrition has been reported to be related to adverse prognosis in acute ischemic stroke (AIS) patients. Unfortunately, traditional nutritional assessment tools usually increase the workload of neurologists, which makes them unfeasible in the daily clinic work. We aimed to elucidate the association between the prognostic nutritional index (PNI), an easily obtainable baseline nutritional marker, and 3-month outcomes in AIS patients receiving intravenous thrombolysis (IVT). Research methods and proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 21 publications
(23 reference statements)
2
47
0
Order By: Relevance
“…Based on the results of our study, it can be said that the prognosis will be much poorer and mortality will be much higher after AIS in patients with malnutrition before the development of AIS. Furthermore, similar to the study conducted by Xiang et al, we revealed that low PNI value in the acute period was associated with mortality in AIS patients 16 . Therefore, measuring the PNI value, which can be easily calculated and does not require additional expenses, in the acute period can be used to determine the short-term prognosis in these patients.…”
Section: Discussionsupporting
confidence: 90%
“…Based on the results of our study, it can be said that the prognosis will be much poorer and mortality will be much higher after AIS in patients with malnutrition before the development of AIS. Furthermore, similar to the study conducted by Xiang et al, we revealed that low PNI value in the acute period was associated with mortality in AIS patients 16 . Therefore, measuring the PNI value, which can be easily calculated and does not require additional expenses, in the acute period can be used to determine the short-term prognosis in these patients.…”
Section: Discussionsupporting
confidence: 90%
“… 7 , 8 The predictive power of this index has also been proved to be high in predicting poor prognosis in subjects with coronary artery disease, acute coronary syndrome, and also stroke. 8 , 11 , 23 However, in the current literature, there is a gap in evidence whether the PNI has an independent predictive power on determining the in-hospital death in COVID-19 cases with cardiovascular risk factors. Our data clearly yielded that after controlling for confounding factors, the PNI was independently related with in-hospital death in such kind of cases.…”
Section: Discussionmentioning
confidence: 99%
“… 7 , 8 Moreover, the prognostic value of this index has been clearly documented in patients with cardiovascular disease, pulmonary embolism, and stroke. 9 , 10 , 11 However, in the current literature, there is a little data whether the PNI has a prognostic value on in-hospital mortality rates in COVID-19 cases with cardiovascular risk factors. Moreover, there is a lack of data in the literature on the comparison of PNI with other accepted prognostic scores such as CURB-65 and 4C mortality risk scores in predicting in-hospital mortality in COVID-19 patients.…”
Section: Introductionmentioning
confidence: 99%
“…The CONUT score was calculated from the levels of three laboratory parameters including serum albumin, lymphocytes, Accepted manuscript and total cholesterol (14) . We set 2 as the cut-off value for CONUT score by a receiver operating characteristics (ROC) curves analysis (Supplementary Figure S1) and categorized the patients into low-CONUT and high-CONUT groups according to the CONUT score: no or low risk of malnutrition (0-1) and high malnutrition risk (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). The NRS-2002 score of ≥ 3 points indicates that the patient is at nutritional risk (23) , considering the impaired nutritional status, the severity of the disease, and the patients' age.…”
Section: Conut Score and Nrs-2002mentioning
confidence: 99%